Physiological values of phagocytic capacity in marine mammals and alterations during pathological situations - Felipo-Benavent, Mar; Martínez-Romero, Alicia; Valls, Mónica; Rojo-Solís, Carlos; Álvaro, Teresa; García-Párraga, Daniel; Rubio-Guerri, Consuelo; O’Connor, José-Enrique (Frontiers in Veterinary Science, 2024)
The study of the immune function in marine mammals is essential to understand their physiology and can help to improve their welfare in the aquariums. Dedicating efforts to studying marine mammal physiology, pathophysiology and implementing new diagnostic and therapeutic tools promote progress towards preventive medicine in aquariums by facilitating early detection and treatment of diseases. However, biological, and clinical research on marine mammals is currently very limited due to difficult access to these species and their biological samples. With this objective, our group has adapted to marine mammals a commercially available assay routinely used to evaluate the phagocytic capacity of monocytes and granulocytes in human whole blood samples. We adapted IngoflowEx kit to bottlenose dolphins (Tursiops truncatus), beluga whales (Delphinapterus leucas), walruses (Odobenus rosmarus), Patagonian sea lions (Otaria flavescens) and harbor (Phoca vitulina). In this paper, we report the modifications carried out on the original protocol for their correct functioning in marine mammals. We obtained physiological values of phagocytic capacity in each species after repeated sampling for 4 years in various individuals of each species. Specific results revealed that the % phagocytic cells that ingested E.coli in bottlenose dolphins were 59.6±1.27, in walruses 62.6±2.17, in sea lions 57.5±4.3, and in beluga whales 61.7±1.4. In the case of the % phagocytic cells producing respiratory burst in bottlenose dolphins were 34.2±3.6, in walruses 36.3±4.3, in sea lions 40.8±10.2, and in beluga whales 26.3±3.7.These preliminary results can be used as a reference to detect alterations in phagocytic capacity either by immunosuppression or by exacerbation of the response in infectious inflammatory processes. Clinical applicability of the assay was verified in two clinical cases in which Ingoflow was useful to detect immune alterations in two diseased individuals, before and after of the onset of clinical signs.